ҚАРАҚАЛПАҚ ҲӘМ ҚЫРҒЫЗ ПРОЗАСЫНДА ӘДЕБИЙ ТӘСИР ҲӘМ ТИПОЛОГИЯ - Каниязова, Ж.О. (SCIENCE and SOCIETY, 2020)
The article provides a comparative analysis of the works of Karakalpak writer Sh. Seytov and Kyrgyz writer Ch.Aitmatov. Based on the analysis, the plot structure and compositional features of the works of both writers are determined, and the similarities in the works are assessed as a product of creative mastery.
Keywords: writer; prose; story; novel; image; hero; dramatic effect; psychologism; retrospection; composition; plot